2014
DOI: 10.1073/pnas.1406853111
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle air quality impacts of conventional and alternative light-duty transportation in the United States

Abstract: Commonly considered strategies for reducing the environmental impact of light-duty transportation include using alternative fuels and improving vehicle fuel economy. We evaluate the air qualityrelated human health impacts of 10 such options, including the use of liquid biofuels, diesel, and compressed natural gas (CNG) in internal combustion engines; the use of electricity from a range of conventional and renewable sources to power electric vehicles (EVs); and the use of hybrid EV technology. Our approach comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
145
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(151 citation statements)
references
References 32 publications
5
145
1
Order By: Relevance
“…Razeghi et al 41 examined the association between power generation, transportation, and air quality in the United States, and they found that O 3 and PM 2.5 decreased with the introduction of wind energy to the grid mix and the use of plug-in electric vehicles. Tessum et al 42 evaluated air quality (PM 2.5 and O 3 )-related human health impacts of fuel type including the use of electric vehicles, and the use of electricity from a range of conventional and renewable sources. The authors found that the health impacts varied by 80% depending on the use of fuel and electricity source.…”
Section: Discussionmentioning
confidence: 99%
“…Razeghi et al 41 examined the association between power generation, transportation, and air quality in the United States, and they found that O 3 and PM 2.5 decreased with the introduction of wind energy to the grid mix and the use of plug-in electric vehicles. Tessum et al 42 evaluated air quality (PM 2.5 and O 3 )-related human health impacts of fuel type including the use of electric vehicles, and the use of electricity from a range of conventional and renewable sources. The authors found that the health impacts varied by 80% depending on the use of fuel and electricity source.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to prior work, we report damages within the county of emission, within the state of emission, and in total (across all receptors). 10 Babaee, Nagpure, and DeCarolis (2014); Graff Zivin, Kotchen, and Mansur (2014); Michalek et al (2011);and Tessum, Hill, and Marshall (2014) analyze the benefits of electric vehicles at the aggregate level. Li et al (forthcoming) consider variation in damages from electric vehicles but assume uniform damages from gasoline vehicles.…”
mentioning
confidence: 99%
“…67,76,107,108 Chinese LCA studies, however, partly quantify CO 2 emission advantages for BEVs in their home country 109 where electricity is largely produced from coal. A collaborative US-Chinese LCA study assessed the use of BEVs in six Chinese provinces as unfavorable with respect to their carbon footprint, which may, however, improve in the future because of advances in power plants' emissions control.…”
Section: Assessing the Carbon Footprint Of Bevs In Chinamentioning
confidence: 99%